Implementing the Merdeka Curriculum: An In-Depth Look at English Teacher’s Obstacles in English Subject - Zahra, Anes Melia; Irfani, Bambang; Hidayat, Agus (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study describes the obstacles English teachers face in implementing the Merdeka Curriculum for 7th and 8th grade at SMPN 18 Bandar Lampung, focusing on the stages of learning planning, learning process, and learning evaluation. The research employed a descriptive qualitative approach, using purposive sampling to select participants. Data were collected through observations and interviews, validated through triangulation techniques, and analyzed using the Miles and Huberman model. The findings reveal various challenges encountered by teachers, including difficulties in designing diagnostic assessments, adapting to student diversity, managing knowledge gaps, addressing students' socio-economic factors and attendance issues, handling low learning motivation, classroom management, limited language proficiency, inadequate facilities, time constraints, and discrepancies between learning processes and student outcomes